Menara 1 Ibu Pejabat Polis Bukit Aman - Rusdi, Muhammad Haniff Hakimi; Mohamad Shahrom, Muhammad Haikal; Azlin, Nur Anisah; Mahadzir, Nur Athirah Batrisyia (2024)
Bukit Aman used to be known as Bluff Road Hill. Before the existence of the Federated Malay States police force, Bluff Road Hill was the headquarters of the Selangor Police Force. Captain H.C. Syers, the Selangor Police Superintendent has moved the Selangor Police Force Headquarters from Klang to Bluff Road due to the rapid development in Kuala Lumpur in addition to the availability of various facilities that make it easier to control the police force more effectively.The Police Force Enactment went into effect in 1903. The concentration of police administration on Bluff Road began with this law. Captain H.L. Talbot was the Police Commissioner at the time this law was in effect